2017
DOI: 10.1097/aap.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Mobile Health Technology in the Treatment of Chronic Pain

Abstract: This article provides a critical overview and best-evidence synthesis of the use of mobile health (mHealth) technology among persons with chronic pain and their health care providers and examines the future benefits and barriers of implementing mHealth technology in clinical care. We critically review articles about electronic pain diaries, pain assessment programs, text messaging, and smartphone pain apps for management of persons with pain. Also presented are findings on the utility of activity trackers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 89 publications
2
47
0
Order By: Relevance
“…In fact, although it has been argued that mobile technology (mHealth)—especially the use of smartphone apps—facilitates this paradigm shift towards telemonitoring in chronic pain care, reviews on this topic have evidenced that randomized controlled trials (RCT) evaluating the usefulness of these tools are lacking in the chronic pain literature [ 39 , 41 , 43 , 44 , 45 ]. Therefore, the current investigation constitutes an important step forward into the literature on this important public health condition.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although it has been argued that mobile technology (mHealth)—especially the use of smartphone apps—facilitates this paradigm shift towards telemonitoring in chronic pain care, reviews on this topic have evidenced that randomized controlled trials (RCT) evaluating the usefulness of these tools are lacking in the chronic pain literature [ 39 , 41 , 43 , 44 , 45 ]. Therefore, the current investigation constitutes an important step forward into the literature on this important public health condition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the five apps that are unusable due to registration and crashing issues are all free apps, and four apps offering high-quality services (our top 4 apps) are all paid apps; these apps are Conclusions drawn from previous studies [12,13,22,23,[14][15][16][17][18][19][20][21] revealed a wide variation in the quality of pain management apps (functions, interface design, and usability) available in the app stores. We found that there is still a great deal of quality variation in the 15 pain apps that were updated or released within the last year.…”
Section: Discussionmentioning
confidence: 99%
“…At least 11 review articles have been published evaluating pain management apps since 2011 [13][14][15][16][17][18][19][20][21][22][23]. Among them, 3 studies deal with specific forms of pain such as low back pain [21], postoperative pain [24], and pediatric pain [18].…”
Section: Introductionmentioning
confidence: 99%
“…To deal with the situation, pain management provides ways to assess and manage pain effectively and improve the quality of life [4]. Mobile technology plays an effective role in pain management by providing mobile applications as a non-pharmacological approach to cope with chronic pain [5][6][7][8]. The role of pain management mobile applications can also contribute to information sharing with patients by educating them for self-management and improving their quality of life [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The role of pain management mobile applications can also contribute to information sharing with patients by educating them for self-management and improving their quality of life [9,10]. However, more studies are required to measure the impact [8]. In this way, better health service and communication could be established between the healthcare professionals and patients [11,12].…”
Section: Introductionmentioning
confidence: 99%